Conflict and conflict management at an institution of juvenile care in the Western Cape Province : the case of Rosendal House (Faure) - Mningiswa, Welder Duma (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.P.A.) -- University of Stellenbosch, 1997.